Heritability and Pedigree Analyses of Hypertrophic Cardiomyopathy in Rhesus Macaques (Macaca Mulatta) - Ueda, Yu; Kovacs, Samantha; Reader, Rachel; Roberts, Jeffrey A.; Stern, Joshua A. (Frontiers in Veterinary Science, 2021)
In a colony of rhesus macaques at California National Primate Research Center (CNPRC), naturally occurring hypertrophic cardiomyopathy (HCM) classified by left ventricular hypertrophy without obvious underlying diseases has been identified during necropsy over the last two decades. A preliminary pedigree analysis suggested a strong genetic predisposition of this disease with a founder effect. However, the mode of inheritance was undetermined due to insufficient pedigree data. Since 2015, antemortem examination using echocardiographic examination as well as other cardiovascular analyses have been performed on large numbers of rhesus macaques at the colony. Based on antemortem examination, HCM was diagnosed in additional 65 rhesus macaques. Using HCM cases diagnosed based on antemortem and postmortem examinations, the heritability (h2) was estimated to determine the degree of genetic and environmental contributions to the development of HCM in rhesus macaques at the CNPRC. The calculated mean and median heritability (h2) of HCM in this colony of rhesus macaques were 0.5 and 0.51 (95% confidence interval; 0.14 – 0.82), respectively. This suggests genetics influence development of HCM in the colony of rhesus macaques. However, post-translational modifications and environmental factors are also likely to contribute the variability of phenotypic expression. Based on the pedigree analysis, an autosomal recessive trait was suspected, but an autosomal dominant mode of inheritance with incomplete penetrance was also possible. Further investigation with more data from siblings, offspring, and parents of HCM-affected rhesus macaques are warranted. Importantly, the findings of the present study support conducting genetic investigations such as whole genome sequencing to identify the causative variants of inherited HCM in rhesus macaques.